Contrast-induced nephropathy; A literature review - Jafar Golshahi; Hamid Nasri; Mojgan Gharipour (Society of Diabetic Nephropathy Prevention, 2014)
Context: Contrast-induced nephropathy (CIN) is a common cause of acute kidney dysfunction. Evidence Acquisitions: Directory of Open Access Journals, Google Scholar, PubMed, EBSCO and Web of Science have been searched. Results: It is necessary to identify at risk patients at early stages to implement preventive strategies to decrease the incidence of this nephropathy. However, mechanisms of CIN have not fully explained yet. It seems that mechanisms which mediated by nitric oxide and prostaglandin-induced vasodilatation have been played a crucial role in the CIN. Hemodynamic changes of renal blood flow, which causes hypoxia in the renal medulla and direct toxic effects of contrast media on renal cells, are thought to contribute to the pathogenesis of CIN. Contrast media is normally divided into iso-osmolar, low-osmolar, and high-osmolar. N-acetylcysteine is considered as one of the best choices to prevent CIN in high-risk groups. Conclusions: The first aim to prevent CIN is identifying high-risk subjects and controlling associate risk factors. As significant differences existed between contrasts agents due to their physicochemical properties, low-osmolar or iso-osmolar contrast media should be used to prevent CIN in at-risk patients. The volume of contrast media should be as low as possible.